Peran Epistemologi Nahwu Dasar dalam Mengonstruksi Kerangka Berpikir Santri Pondok Imam Bukhari terhadap Pemahaman Nash Al-Qur'an yang Benar Sosial sebagai Landasan Psikologis Muncul - Mujiburrohman, Mujiburrohman; Muhammad, Faiz Rasyid (TSAQOFAH, 2026)
In Islamic studies, basic nahwu is often regarded merely as a technical linguistic tool, whereas epistemologically this discipline functions as a logical foundation for unpacking the structure of meaning in revealed texts. This study aimed to reveal the epistemological significance of basic nahwu in shaping the methodological thinking patterns of santri at Pondok Pesantren Imam Bukhari. A qualitative method with a descriptive-analytical approach was employed to evaluate how the internalisation of fundamental rules, such as mastery of i‘rāb and the functional positions of words, influences the way santri deduce meaning from the naṣṣ of the Al-Qur’an. The findings show that mastery of basic nahwu contributes significantly to constructing santri’s thinking framework in three main aspects: (1) accuracy, by minimising interpretive errors caused by changes in final vowels (harakat); (2) logic, by habituating systematic thinking based on the relationships among subject (fā‘il), object (maf‘ūl), and predicate (fi‘l); and (3) authority, by building santri’s scholarly confidence to refer directly to primary sources. In conclusion, basic nahwu is not merely a linguistic prerequisite but an essential epistemic instrument for safeguarding the authenticity of Al-Qur’an understanding from speculative interpretations.